Historia dicax : rire, discours et rhétorique chez Tite-Live - Benoît Sans (Methodos, 2023)
The present study gathers the passages of Livy’s Ab Vrbe condita where the lexicon of laughter is associated with a speech or spoken words, in order to confront them on Cicero’s and Quintilian’s views on laughter in a rhetorical context. If all the passages fit with such conception of laughter, the Latin historian also uses it to create an original distribution of acceptable and abusive forms of laughter which plays a role in the construction of the characters’ portraits and the work as a whole.